Daily Controlled Consumption of an Electrokinetically Modified Water Alters the Fatigue Response as a Result of Strenuous Resistance Exercise. (7th May 2014) - Borsa, Paul A.; Larkin-Kaiser, Kelly A.
Abstract : Our objective was to assess the effects of consuming electrokinetically modified water (EMW) on fatigue attenuation and ratings of perceived exertion (RPE) following resistance exercise. A double-blind, placebo-controlled, two-arm trial was used in this investigation. Forty participants were randomly assigned to either an experimental or a placebo-control group. Participants consumed the EMW or placebo water daily for eighteen days prior to completing a fatigue protocol for the elbow flexors. The fatigue protocol consisted of a single bout of resistance exercise for the biceps brachii. Participants were tested for isometric strength before exercise and immediately following exercise. The maximal voluntary isometric contraction was used as the criterion measure for strength. To calculate the fatigue index, the postexercise maximal voluntary isometric contraction value was divided by the preexercise maximal voluntary isometric contraction value multiplied by 100. Also, ratings of perceived exertion (RPE) were assessed using the Borg scale. Fatigue indices and RPE were significantly lower for the experimental group compared to the control group (P < 0.05 ). Consuming EMW for eighteen days prior to high intensity resistance exercise can significantly enhance muscle contractile function by reducing muscle fatigue and RPE.